2019
DOI: 10.18061/bhac.v3i1.6678
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Meditation Among College Students: The Role of Personality Traits

Abstract: Background: Meditation is likely to be a useful intervention for anxiety and depression, and is increasingly common as a clinical intervention and informal practice among university students.  However, meditation dropout rates are high, and it is likely that perceived barriers to meditation play a role.  While neuroticism is known to predict dropout, there has been no study relating personality traits to these barriers.Aim: To better understand the barriers to meditation practice that university students exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…While some statistical approaches can help identify non‐linear systems (e.g. Whitford & Warren, 2019; Wolf‐Branigin, 2013), other approaches may be better‐suited to studying non‐linear phenomena. Common techniques used to examine CAS include machine learning, geographic information systems (GIS), social network analysis and computer simulation models (Cioffi‐Revilla, 2010; Furtado & Sakowski, 2015; Morçöl, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…While some statistical approaches can help identify non‐linear systems (e.g. Whitford & Warren, 2019; Wolf‐Branigin, 2013), other approaches may be better‐suited to studying non‐linear phenomena. Common techniques used to examine CAS include machine learning, geographic information systems (GIS), social network analysis and computer simulation models (Cioffi‐Revilla, 2010; Furtado & Sakowski, 2015; Morçöl, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…(18,19)) have been shown to predict MRA, such that conscientiousness and agreeableness are positively related to MRA, whereas neuroticism is negatively related to MRA (20,21). Neuroticism has also been linked to the perception of greater barriers to meditation (22). One study using personality to predict the frequency of engagement in MBSR activities both during and after the intervention found that openness and agreeableness were significant predictors (23).…”
Section: Factors Predicting Mramentioning
confidence: 99%
“…The openness subscale (10 items; pre, post, 3-month: α = .79, .77, .82) measures traits such as curious, imaginative, artistic, wide interests, excitable, and unconventional. The extraversion scale was not included in analysis because of a lack of association with MRA in previous studies (20)(21)(22)(23).…”
Section: Trait Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…People with mental health problems (e.g., depression) may feel helpless, i.e., that there is nothing that can be done to improve their mental health (Seligman 1974), which may hinder uptake of mindfulness practice. Indeed, quantitative studies have found that various mental health problems are associated with meditation program attrition or perceived barriers to meditation (Banerjee et al 2018;Crane and Williams 2010;Delmonte 1980Delmonte , 1984Delmonte , 1988Whitford and Warren 2019;Williams et al 2012;Williams et al 1976). Other studies have found that intention or practice itself is not associated with severity of problems (Bistricky et al 2018;Rizer et al 2016).…”
mentioning
confidence: 99%